2019
DOI: 10.3389/fbioe.2019.00329
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Quality of Life and Acceptability of Disability in Patients With Facial Burn Scars

Abstract: The purpose of our research is to understand the status of the quality of life and level of disability acceptance in patients with facial burn scars and to explore the correlation between quality of life and disability acceptance and how to improve nursing care for these patients. Patients with facial burn scars were investigated in an outpatient clinic of tertiary hospitals from September 2015 to February 2016. A cross-sectional survey was conducted. The questionnaires used included demographic data and inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Acceptance of disability, a signi cant element in psychosocial adaptation, refers to through shifts of value system, an individual perceives that the losses caused by disability do not impair the existing normal abilities and meaning of existence [8]. Former studies showed a signi cant correlation between acceptance of disability and quality of life among patients with different chronic diseases [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Acceptance of disability, a signi cant element in psychosocial adaptation, refers to through shifts of value system, an individual perceives that the losses caused by disability do not impair the existing normal abilities and meaning of existence [8]. Former studies showed a signi cant correlation between acceptance of disability and quality of life among patients with different chronic diseases [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing interest in the long term psychosocial effects of burn injury research that focuses on the quality of life (1)(2)(3)(4). Similar interest is also observed in the head and neck burn research where new reports relating to the quality of life of facial are published in recent years (5)(6)(7).…”
Section: Introductionmentioning
confidence: 83%
“…Similarly, a study from Poland also found that disease acceptance significantly affected QoL ( 28 ). Higher AOD level was also found to contribute significantly to higher overall QoL in patients with colostomy ( 38 ), facial burn scar ( 39 ), epilepsy ( 40 ), and stroke ( 41 ). First, emotionally, improvement in AOD level changes the cognition of PD patients, promotes their control over their own emotions, allows them to perceive more positive psychological emotions, and thus their attitude toward life.…”
Section: Discussionmentioning
confidence: 99%